An Integrative Linear Mixed Modeling Approach to Batting Performance in Cricket: Examining Ball Opportunities, Run Production, Match Context, and Individual Variability - Fadhli, Nurrul Riyad; Hariadi, Imam; Taufik, Taufik; Yuniarto, Andryas; Yanto, Nanda Dwi (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose. Batting evaluation in cricket is still dominated by conventional indicators such as total score, which potentially simplifies the performance-building mechanism and fails to integrate the relationships between balls, runs, run type, innings, match type, and individual athlete variation. This study aims to analyze the characteristics of performance distribution, the relationship between run type and innings, and the influence of match context using an integrative analytical framework. Materials and methods. The study employed a retrospective observational design with a total-event sampling approach on 601 valid batting observations from all available match events. Analysis was conducted using descriptive statistics, performance distribution visualization, the Chi-Square test, and a Linear Mixed Model (LMM). The LMM approach was used to accommodate the multilevel data structure, repeated measurements, fixed effects, and individual athlete variation as random effects. Result. The results show high heterogeneity in batting performance, marked by significant variation in ball and run distribution. Boundary scoring (4 runs and 6 runs) contributed more to the score than single runs, indicating a tendency toward aggressive play strategies in scoring. A significant relationship was found between run type and innings, although the effect size was relatively small. Linear Mixed Model results showed that match type and innings had no significant effect after individual athlete variation was accounted for. Conclusion. Cricket batting performance is a multidimensional phenomenon shaped by the dynamic interaction of playing opportunities, scoring efficiency, match context, and individual athlete characteristics. These findings suggest that individual dynamics contribute more to performance formation than the general match context, supporting the use of integrative approaches and multilevel models in modern sports performance analysis.